The effect of RAFT strategy on improving EFL descriptive writing skills among 9th-grade EFL students from a non-bilingual private school in Daule. - Espinoza Valenzuela, Meyling Milen (2025)
This study examines the effect of the RAFT (Role, Audience, Format, Topic) strategy on improving EFL content development skills for descriptive writing among 9th-grade EFL students in a non-bilingual private school in Daule. This research employs a pre-experimental one-group pretest and posttest design with a mixed-method approach to analyze both quantitative and qualitative data. The study was conducted with a single 9th-grade class, where students were exposed to the RAFT strategy as part of their writing instruction. Qualitative data was collected through observations. Quantitative data was gathered from surveys. Additionally, mixed data was collected using checklists and tests as writing assessment. The findings indicate that after implementing the RAFT strategy, students demonstrated moderate improvement in content development, creativity, and engagement in their writing compared to their initial performance before using the strategy. Based on these results, recommendations are provided for integrating RAFT into writing instruction to support EFL learners in developing their descriptive writing skills.